2020
DOI: 10.18502/ijph.v49i8.3910
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Link between COVID-19 Mortality with Genus, Age, ABO Blood Group Type, and ACE2 Gene Polymorphism?

Abstract: The article's abstract is no available.  

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The results are inconsistent. However, it seems that the risk of COVID-19 is positively associated with A blood group compared with O phenotype [ 17 , 18 , 24 , 26 , 28 ]. Our present finding, confirmed the relationship of ABO genetic system with susceptibility to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The results are inconsistent. However, it seems that the risk of COVID-19 is positively associated with A blood group compared with O phenotype [ 17 , 18 , 24 , 26 , 28 ]. Our present finding, confirmed the relationship of ABO genetic system with susceptibility to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…( A ) Blood group O odd ratios (ORs) of COVID-19 relative to the other blood groups and blood group O frequencies at various geographical locations. Odd ratios were obtained from the works in [ 1 , 2 , 3 , 6 , 9 , 10 , 11 , 14 , 17 , 18 , 19 , 22 , 24 ], and the frequencies of blood group O were those reported in the groups of controls of the corresponding studies, representing frequencies in the local populations. OR values in populations where frequencies of blood group O are below and above 40% (O < 0.4 and O > 0.4, respectively) were compared by a two-tailed Mann–Whitney test.…”
Section: Figurementioning
confidence: 99%
“…Thus, soon after the beginning of the pandemic a publication from Wuhan, China, reported a higher risk of infection for people of blood group A, and inversely a lower risk for people of blood group O [ 1 ]. Since then, associations with the ABO blood groups have been described in several additional publications from China as well as many other locations from Asia, the Middle East, Europe, and North America [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Associations between ABO phenotypes were described with either the risk of infection or disease severity, although most studies did not explicitly separate these two aspects.…”
Section: Introductionmentioning
confidence: 99%
“…It is now rather well documented through a large set of studies that blood group A individuals are at a higher risk of COVID-19 than individuals of blood group O, whilst blood group B seldom shows significant odd ratios relative to the other blood groups ( Aktimur et al, 2020 ; Barnkob et al, 2020 ; Chegni et al, 2020 ; Ellinghaus et al, 2020 ; Göker et al, 2020 ; Latz et al, 2020 ; Leaf et al, 2020 ; Li et al, 2020 ; Muniz-Diaz et al, 2020 ; Shelton et al, 2020 ; Sohlpour et al, 2020 ; Valenti et al, 2020 ; Wu et al, 2020 ; Zeng et al, 2020 ; Zhang et al, 2020 ; Zhao J. et al, 2020 ; Zietz et al, 2020 ). We recently observed that anti-A and anti-B agglutinating natural antibodies were significantly lower in COVID-19 patients compared with controls ( Deleers et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, group O individuals possess anti-A and anti-B antibodies that could have protected them from viral particles emitted by either blood group A or B patients. Interestingly, a large number of observations indicate that blood group O individuals have a lower risk of COVID-19, whereas blood group A individuals appear to be at a higher risk ( Cheng et al, 2005 ; Abdollahi et al, 2020 ; Ahmed et al, 2020 ; Aljanobi et al, 2020 ; Barnkob et al, 2020 ; Chegni et al, 2020 ; Delanghe et al, 2020 ; Dzik et al, 2020 ; Ellinghaus et al, 2020 ; Fan et al, 2020 ; Franchini et al, 2020 ; Gallian et al, 2020 ; Göker et al, 2020 ; Hoiland et al, 2020 ; Latz et al, 2020 ; Leaf et al, 2020 ; Li et al, 2020 ; Muniz-Diaz et al, 2020 ; Niles et al, 2020 ; Padhi et al, 2020 ; Ray et al, 2020 ; Roberts et al, 2020 ; Shelton et al, 2020 ; Sohlpour et al, 2020 ; Valenti et al, 2020 ; Wu et al, 2020 ; Zeng et al, 2020 ; Zhang et al, 2020 ; Zhao J. et al, 2020 ; Zietz et al, 2020 ). Only a few studies failed to find any association between ABO types and COVID-19, likely depending on study design ( Boudin et al, 2020 ; Focosi et al, 2020 ; Pairo-Castineira et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%